RELATIONSHIP OF ACHIEVEMENT MOTIVATION WITH MATHEMATICAL LEARNING ACHIEVEMENTS IN CLASS VIII OF SMP 6 PALOPO - Fatimah Fatimah (USN Kolaka, 2019)
This study aims to (1) obtain an overview of the level of achievement motivation of class VIII students of SMP 6 Palopo (2) Know the level of mathematics learning achievement of class VIII students of SMP 6 Palopo. 6 Palopo. The method used in this study is a questionnaire and test of learning outcomes. The results showed that the average score of student achievement motivation was 20.05 from the ideal score of 26 and the standard deviation of 2.27 including the medium category, the average score of students' mathematics learning achievement 75.81 from the ideal score of 100 with a standard deviation of 6.26 including the medium category. It can be concluded that there is a positive relationship between achievement motivation and mathematics learning achievement of class VIII Palopo 6 SMP with a correlation coefficient of 0.72 and efficiency determination of 0.52 (52%).